Rigoletto [an opera in three acts] - Verdi, Giuseppe 1813-1901 (Opera Australia, 2011)
One of Opera Australia's best-loved productions, Elijah Moshinsky's retelling of Rigoletto draws Verdi's dark melodrama into a modern day mafioso underworld, inspired by Federico Fellini's all-time classic La Dolce Vita. Heading a glittering international cast is baritone Alan Opie in a commanding performance as the tortured jester, with Emma Mathews taking on the role of Gilda and Paul O'Neil as the lustful Duke. Conductor Giovanni Reggioli sympathetically captures the luscious yet fragile tones of Verdi's much-loved scrore, with it feast of sublime singing